2017
DOI: 10.15390/eb.2017.6911
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Experiences in a Professional Learning Community on The Constructivist Lesson Planning: A Case Study Among Primary School Teachers

Abstract: Çalışmanın amacı, öğretmenlerin mesleki öğrenme topluluğu uygulamalarına ilişkin görüşlerinin belirlenmesi ve bu uygulamanın yapılandırmacı ders planı hazırlama becerisi ile yapılandırmacılık ve yapılandırmacı ders planı anlayışlarında oluşturduğu değişimin incelenmesidir. Araştırmada sekiz haftalık bir süreçte yapılandırmacı anlayışa dayalı ders planı hazırlama konusunda yürütülen mesleki öğrenme topluluğu uygulaması örnek olay olarak ele alınmıştır. İlkokul düzeyinde görev yapmakta olan dört sınıf öğretmeni … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The making of this module uses a constructivist learning approach, so this module is called an ethno constructivist module. [14] The constructivist learning processes support students' active participation, knowledge construction, and deep learning, encourage students to think and act independently, and foster permanent learning.…”
Section: Resultsmentioning
confidence: 99%
“…The making of this module uses a constructivist learning approach, so this module is called an ethno constructivist module. [14] The constructivist learning processes support students' active participation, knowledge construction, and deep learning, encourage students to think and act independently, and foster permanent learning.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Gul (2016) found that teacher development seminars, which aimed at developing awareness of the importance of professional development, resulted in a positive change in teachers' constructivist views, approaches, and practices. Colak (2017) states that professional learning communities yielded a change in teachers' lesson plans towards a more constructivist approach. Similarly, Mansour (2013) underlines that the classroom and school social communities should be transformed into more active learning communities so that a constructivist viewpoint could be adopted in science teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Apply it with question and answer. (Teacher interview, November 14, 2018); (10) Etnosocial is a new thing. In grade 3 there are no IPS.…”
Section: Regressionmentioning
confidence: 99%
“…The study of how significantly the influence of a teacher's age on his competence is very rare. The reason according to Sloane & Kelly [10] is that most developed countries like America don't care about the age of a teacher. But in this study, it will be seen whether the teacher's age influences the teacher's pedagogical competence.…”
Section: Introductionmentioning
confidence: 99%